Efficacy of Shot-Blocker in Alleviating Peripheral Intravenous Cannulation Associated Pain among Hospitalized School-Aged Children - A. Naser, Salsabeel; AL-Fayyadh, Sadeq Abdul-Hussein Hassan (Iraqi National Journal of Nursing Specialties, 2026)
Objective(s): Examining the effect of Shot-Blocker in reducing Peripheral Intravenous Cannulation (PIV) associated pain among school age children’s patients. Methods: This study used a prospective, comparative, randomized controlled trial design. The study involved 153 school aged children (6-12 years) who received intravenous cannulation at Emergency Departments in Wasit: Al-Azizia and Al-Numaniyah General Hospital between January 22nd, and February 21st, 2024. Patients were randomly divided into two groups: the Shot-Blocker group (n=79), and control group (n=74). The Peripheral Intravenous Cannulation process was followed by a request for the patients to rate their level of pain using the Wong–Baker Faces Pain Scale. The primary outcome was to reduce pain related to intravenous cannulation for school age children. A descriptive and inferential statistical measures were employed in the analysis of the data through the using IBM-SPSS. The group’s differences in levels of pain were measured using an independent sample t-test. Result: There are statistically significant differences in pain intensity between the Shot-Blocker, and control group (P-value=0.001*). When compared to the control group, Shot-Blocker group showed a markedly reduced pain intensity (mean difference 1.74684). In addition, there were higher pain levels noted in the control group (mean difference 8.757) compared to the Shot-Blocker group. Conclusions: The Shot-Blocker technique was efficient to reduce pain-related intravenous-cannulation. Most children using Shot-Blocker experienced less pain compared to those who did not. This suggests that innovative non-pharmacological approaches like Shot-Blocker are advantageous for pain reduction.